Dampak Kekerasan Seksual terhadap Psikologis Perempuan - Nazwa Aulia Khairunnisa; Farsya Nafilah Haryanto; Najwa Tazkiyatu Nufus; Ati Kusmawati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Sexual violence  against women  is a serious issue the  leaves deep traumatic impacts and significantly affects the mental health of the victims. This research aims to investigate the psychological impact experienced by women who are victims of sexual violence. The main focus of research includes post-traumatic stress disorder (PTSD), anxiety, depression, sense of  meaning,  and decreased self-esteem. The methodology of this research applies a qualitative approach by conducting a literature review of various journals, reports, and related articles. The research results show that sexual violence not only causes physical suffering but also significantly impacts the emotional and mental stability of the victims over a long period. Therefore, social  support, counselling service, and psychological assistance are essential elements in the healing process. This study is expected to enhance public understanding of the impact of sexual violence and encourage the formulation of more effective policies in handling and preventing similar cases.